2022
DOI: 10.3390/app12189034
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Rotary Friction-Welded Tungsten and Mild Steel Joints

Abstract: This paper is a study of the microstructure and other selected properties of solid-state, high-speed, rotary friction-welded tungsten and mild steel (S355) joints. Due to the high affinity of tungsten for oxygen, the welding process was carried out in a chamber with an argon protective atmosphere. Joints of suitable quality were obtained without any macroscopic defects and discontinuities. Scanning electron microscopy (SEM) was used to investigate the phase transformations taking place during the friction weld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…According to the research results, the remarkable findings provide potential industrial values in the polymer-welding industry, since the RFW of dissimilar polymer rods is a green manufacturing method based on four sustainable development goals, i.e., SDGS 7, 8, 9, and 12 [33][34][35][36][37]. In particular, the RFW of polymer rods can be applied for joining the fluid me- According to the research results, the remarkable findings provide potential industrial values in the polymer-welding industry, since the RFW of dissimilar polymer rods is a green manufacturing method based on four sustainable development goals, i.e., SDG S 7, 8, 9, and 12 [33][34][35][36][37]. In particular, the RFW of polymer rods can be applied for joining the fluid mechanical components, automotive components, axle shafts, or aerospace components [38,39].…”
Section: Resultsmentioning
confidence: 90%
“…According to the research results, the remarkable findings provide potential industrial values in the polymer-welding industry, since the RFW of dissimilar polymer rods is a green manufacturing method based on four sustainable development goals, i.e., SDGS 7, 8, 9, and 12 [33][34][35][36][37]. In particular, the RFW of polymer rods can be applied for joining the fluid me- According to the research results, the remarkable findings provide potential industrial values in the polymer-welding industry, since the RFW of dissimilar polymer rods is a green manufacturing method based on four sustainable development goals, i.e., SDG S 7, 8, 9, and 12 [33][34][35][36][37]. In particular, the RFW of polymer rods can be applied for joining the fluid mechanical components, automotive components, axle shafts, or aerospace components [38,39].…”
Section: Resultsmentioning
confidence: 90%
“…In previous works, Skowrońska et al [ 29 ] found that the character of the weld in a dissimilar joint is based on deep plastic deformation without visible diffusive processes in the interface zone. Xie et al [ 30 ] analysed the effects of welding parameters on microstructure, tensile strength, and microhardness in RFWed joints produced without upset forging on pure molybdenium rods.…”
Section: Introductionmentioning
confidence: 99%
“…Hangai et al have attempted to join porous aluminum fabricated by the sintering and dissolution process (SDP) [22][23][24][25][26] to polycarbonate (PCTA) and acrylic resin plates by friction welding [27][28][29]. Friction welding [30,31] is a simple and productive joining method, which is one of the solid-state welding methods [32][33][34][35], allowing strong joining without melting the material. The porous aluminum is rotated at a high rotating rate and pressed against the PCTA plate to soften the PCTA by frictional heat, which allows the PCTA to penetrate the pores, joining them by the anchor effect.…”
Section: Introductionmentioning
confidence: 99%